Pious pilgrims, discerning travellers, curious tourists : changing patterns of travel to the Middle East from medieval to modern times - Starkey, Paul, 1947-; Starkey, Janet, 1948- (Astene publications., 2020)
This volume comprises a varied collection of seventeen papers presented at the biennial conference of the Association for the Study of Travel in Egypt and the Near East (ASTENE) held in York in July 2019, which together will provide the reader with a fascinating introduction to travel in and to the Middle East over more than a thousand years.